The Influence of Posting Frequency, Content Quality, and Interaction with Customers on Social Media on Customer Loyalty in a Start-up Business - Mufadhol Mufadhol; Fauzia Tutupoho; Deflin Tresye Nanulaita; Ann Z. de Bell; Bagus Prabowo (West Science Business and Management, 2024)
This research investigates the impact of posting frequency, content quality, and interaction with customers on social media on customer loyalty in start-up businesses. A quantitative approach is employed, with data collected from 190 start-up owners or marketing professionals responsible for managing social media accounts. Structural Equation Modeling with Partial Least Squares (SEM-PLS) is used for data analysis. The findings reveal significant positive relationships between posting frequency, content quality, interaction with customers, and customer loyalty. Content quality emerges as a strong predictor of customer loyalty, highlighting the importance of creating engaging and relevant content. Active interaction with customers on social media platforms also positively influences customer loyalty, fostering stronger relationships and brand advocacy. While posting frequency plays a role in maintaining brand visibility, the quality and relevance of content are found to be paramount. These findings have practical implications for start-up businesses seeking to enhance customer loyalty through effective social media engagement strategies.